LncRNA NCAL1 potentiates natural killer cell cytotoxicity through the Gab2-PI3K-AKT pathway - Niu, Chao; Li, Min; Chen, Yongchong; Zhang, Xiaoying; Zhu, Shan; Zhou, Xin; Zhou, Lei; Li, Zhaozhi; Xu, Jianting; Hu, Ji-fan; Wang, Yufeng; Cui, Jiuwei (Frontiers in Immunology, 2022)
Natural killer (NK) cells perform immune surveillance functions in tumors. The antitumor effects of NK cells are closely related to tumor occurrence and development. However, the molecular factors that determine NK cell antitumor activity remain to be characterized. In the present study, we identified a novel long noncoding RNA (lncRNA), NK cell activity-associated lncRNA 1 (NCAL1), and investigated its function in NK cells. NCAL1 was primarily located in NK cell nuclei, where it functioned by activating Gab2, a scaffold protein with an essential role in immune cells. Gab2 positively regulated the killing activity of NK cells. Mechanistically, NCAL1 upregulated Gab2 epigenetically by binding to the Gab2 promoter, which decreased methylation, recruited the transcription factor Sp1, and increased H3K4me3 and H3K27ac levels in the Gab2 promoter. Furthermore, NCAL1 enhanced the cytotoxicity of NK cells toward tumor cells through the Gab2-PI3K-AKT pathway. Thus, NCAL1 potentiates NK cell cytotoxicity and is a promising therapeutic target to improve NK cell therapy.